AB0007 The CD226 gene is not involved in giant cell arteritis in the spanish caucasian population. (23rd January 2014) - Serrano, A.; Carmona, D.; Miranda-Filloy, J.A.; Castañeda, S.; Rodríguez-Rodríguez, L.; Morado, I.; Gόmez-Vaquero, C.; Solans, R.; Sopeña, B.; Blanco, R.; Unzurrunzaga, A.; Ortego-Centeno, N.; et al.
Abstract : Background: CD226 genetic variants have been associated with a number of autoimmune diseases. Objectives: The aim of this study was to investigate the potential implication of the CD226 loci in the susceptibility to and main clinical manifestations of giant cell arteritis (GCA). Methods: A Spanish Caucasian cohort of 455 patients diagnosed with biopsy-proven GCA and 1414 healthy controls were included in the study. Three CD226 polymorphisms, rs727088, rs34794968 and rs763361, were genotyped using the TaqMan® allelic discrimination technology. PLINK software was used for the statistical analyses. Results: No significant association between the CD226 polymorphisms and susceptibility to GCA was found (rs727088: P =0.92, OR=1.01 CI 95% 0.86-1.18; rs34794968: P =0.61, OR=1.04 CI 95% 0.89-1.22; rs763361: P =0.88, OR=0.99 CI 95% 0.84-1.16). Similarly, when patients were stratified according to the specific clinical features of GCA such as polymyalgia rheumatica, visual ischemic manifestations or irreversible occlusive disease, no association was observed either between the case subgroups and the control set or between GCA patients with and without the specific features of the disease. Furthermore, the haplotype analysis revealed no significant association with the disease. Conclusions: Our results show that the CD226 gene does not play a relevant role in the susceptibility to GCA and clinical manifestations of this vasculitis. References: Hafler JP, Maier LM, Cooper JD, Plagnol V, Hinks A, Simmonds MJ, et al. CD226 Gly307Ser association with multiple autoimmune diseases. Genes Immun. 2009; 10:5-10. Lofgren SE, Delgado-Vega AM, Gallant CJ, Sanchez E, Frostegard J, Truedsson L, et al. A 3'-untranslated region variant is associated with impaired expression of CD226 in T and natural killer T cells and is associated with susceptibility to systemic lupus erythematosus. Arthritis Rheum. 2010; 62:3404-3414. Salvarani C, Cantini F, Boiardi L, Hunder GG. Polymyalgia rheumatica and giant-cell arteritis. N Engl J Med. 2002; 347:261-271. Gonzalez-Gay MA, Vazquez-Rodriguez TR, Lopez-Diaz MJ, Miranda-Filloy JA, Gonzalez-Juanatey C, Martin J, et al. Epidemiology of giant cell arteritis and polymyalgia rheumatica. Arthritis Rheum. 2009; 61:1454-1461. Disclosure of Interest: None Declared